Ghrelin O-acyltransferase knockout mice show resistance to obesity when fed high-sucrose diet. Issue 2 (8th December 2015) - Kouno, Tetsuya; Akiyama, Nobuteru; Ito, Takahito; Okuda, Tomohiko; Nanchi, Isamu; Notoya, Mitsuru; Oka, Shogo; Yukioka, Hideo
Abstract : Ghrelin is an appetite-stimulating hormone secreted from stomach. Since the discovery that acylation of the serine-3 residue by ghrelin O -acyltransferase (GOAT) is essential for exerting its functions, GOAT has been regarded as an therapeutic target for attenuating appetite, and thus for the treatment of obesity and diabetes. However, contrary to the expectations, GOAT-knockout (KO) mice have not shown meaningful body weight reduction, under high-fat diet. Here, in this study, we sought to determine whether GOAT has a role in body weight regulation and glucose metabolism with a focus on dietary sucrose, because macronutrient composition of diet is important for appetite regulation. We found that peripherally administered acylated-ghrelin, but not unacylated one, stimulated sucrose consumption in a two-bottle-drinking test. The role of acylated-ghrelin in sucrose preference was further supported by the finding that GOAT KO mice consumed less sucrose solution compared with WT littermates. Then, we investigated the effect of dietary composition of sucrose on food intake and body weight in GOAT KO and WT mice. As a result, when fed on high-fat diet, food intake and body weight were similar between GOAT KO and WT mice. However, when fed on high-fat, high-sucrose diet, GOAT KO mice showed significantly reduced food intake and marked resistance to obesity, leading to amelioration of glucose metabolism. These results suggest that blockade of acylated-ghrelin production offers therapeutic potential for obesity and metabolic disorders caused by overeating of palatable food.